Participation in Physical Activity at Time of Presentation to a Specialty Concussion Clinic Is Associated With Shorter Time to Recovery. Issue 12 (3rd September 2020) - Coslick, Alexis M.; Chin, Kaitlyn E.; Kalb, Luther G.; Slomine, Beth S.; Suskauer, Stacy J.
Abstract : Introduction: Novel research suggests that children engaging in physical activity during recovery from concussion may recover more rapidly. Objective: To determine if level of physical activity at presentation to a rehabilitation‐based concussion specialty clinic predicted days from injury to recovery. Design: Retrospective cohort. Setting: A concussion sub‐specialty clinic at an academic institution. Patients: Retrospective review of medical records between September 2015 and February 2017 identified 178 children ages 6‐17 years (mean age = 13.7 years; standard deviation [SD] = 2.7 years) who presented within 60 days of concussion and were ultimately deemed recovered and cleared to progress to full return to high‐risk activities. Interventions: Not applicable. Main Outcome Measures: Physical activity at initial visit was classified as none‐to‐light (79%) versus moderate‐to‐heavy (21%). A doubly robust, inverse probability of exposure weighted linear regression model was used to examine the relationship between physical activity level and days to recovery, while adjusting for 10 demographic and clinical variables. Results: Children participating in moderate‐to‐heavy activity at initial evaluation in concussion clinic averaged recovery 21 days quicker (95% confidence interval [CI] −27.1, −15.5, P  < .001) than children who were engaging in none‐to‐light activity. This finding did not change when removing children who were deemed recovered at the first visit (who may have initiated physical activity after becoming asymptomatic). Conclusions: These data add to growing evidence that progressive physical activity during recovery from concussion does not appear to be harmful. Physical activity represents a modifiable variable in recovery, and physicians can potentially expedite symptomatic recovery by recommending noncontact physical activity as tolerated during concussion recovery.